Essays on shareholders' value and new product strategies - Ik, Kuen Hwa (2008)
Many finance and marketing studies have examined the valuation effect of new product strategy in a static framework and tend to overlook the importance of competitive dynamism. This dissertation intends to explore several important issues in new product competition, such as firm's opportunities and strategic behaviors. This dissertation is divided into three essays: (1) the wealth effect of new product introductions on industry rivals; (2) strategic competition and firm values; and (3) the valuation of new product introductions under uncertain competition: a real option approach. In general, variables that are important in determining the real option values are present value of the project cash flows, option life, project value's uncertainty, and speed of adjustment. The results also indicate that the value of product development opportunities is higher (1) when the opportunities is in the more volatile environment, (2) when the window of opportunities is longer, and (3) when the competitive intensity is lower.